Thirteen new species of Graphidaceae (lichenized Ascomycota: Ostropales) from Sri Lanka - Weerakoon, Gothamie; Lücking, Robert; Lumbsch, H. Thorsten (Phytotaxa, 2014)
Based on further study of collections of Graphidaceae originating from Sri Lanka, thirteen new species are described: Acanthothecis aurantiacodiscus G. Weerakoon, Lücking & Lumbsch, differing from A. socotrana in the corticate thallus, larger and broader ascomata with orange disc, and larger ascospores; Chapsa isidiata G. Weerakoon, Lücking & Lumbsch, characterized by a yellowish, isidiate thallus; Halegrapha masoniana G. Weerakoon, Lücking & Lumbsch, differing from other species of Halegrapha in the combination of inspersed hymenium and norstictic acid chemistry, as well as the comparatively large ascospores; Leucodecton canescens G. Weerakoon, Lücking & Lumbsch, with grey thallus and rather large, black-rimmed ascoma pores; L. fuscomarginatum G. Weerakoon, Lücking & Lumbsch, differing from L. coppinsii in the immersed ascomata and larger ascospores; Ocellularia aptrootiana G. Weerakoon, Lücking & Lumbsch, differing from O. pluriporoides in the less prominent, regularly rounded ascomata with broad white rim, the brown (uncarbonized) columella, and the smaller ascospores; O. balangoda G. Weerakoon, Lücking & Lumbsch, differing from O. mauritiana in the more regular, apically carbonized columella; O. cloonanii G. Weerakoon, Lücking & Lumbsch, differing from O. pluripora in the ascomata with broader pore, the apically carbonized columella, and the larger ascospores; O. raveniana G. Weerakoon, Lücking & Lumbsch, differing from O. laeviuscula in the distinct columella and the hyaline, transversely septate ascospores; Platythecium sripadakandense G. Weerakoon, Lücking & Lumbsch, with pseudostromatic lirellae and norstictic acid chemistry; Rhabdodiscus isidiatus G. Weerakoon, Lücking & Lumbsch, characterized by a cream-white thallus with robust isidia and by small, 3-septate ascospores; R. parnmenianus G. Weerakoon, Lücking & Lumbsch, with immersed, annulate ascomata and submuriform, hyaline ascospores; and Thalloloma pedespulli G. Weerakoon, Lücking & Lumbsch, differing from T. haemographum in the larger ascospores. The new combination Leucodecton coppinsii (Homchant.) G. Weerakoon, Lücking & Lumbsch is also proposed. The considerable diversity of Graphidaceae in Sri Lanka is placed into perspective given the destruction of most of the natural rain forest habitats typical for this family and many other organisms.